1991
DOI: 10.1104/pp.95.3.839
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Synthesis by Bundle Sheath Cells of Maize

Abstract: Because in the phloem sap of maize (Zea mays L.) leaves a quarter of the total amino nitrogen can be found as alanine, the capacity of a de novo synthesis of alanine from 3-phosphoglycerate (3-PGA) was studied with isolated bundle sheath (BS) strands of maize. Inasmuch as these cells have retained their plasmodesmatic openings, it was possible to study the formation of alanine from 3-PGA when glutamate and ADP were being added. Alanine synthesis required the existence of the intact cell structure. From the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

1992
1992
1999
1999

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
2
11
0
1
Order By: Relevance
“…Recently, the permeability of isolated bundle-sheath cells from maize has been utilized to differentiate between possible pathways for alanine biosynthesis (Valle and Heldt 1991). In animal systems, channeling of glycolytic intermediates has been demonstrated using mouse L-929 cells permeabilized with dextran sulfate (Clegg and Jackson 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the permeability of isolated bundle-sheath cells from maize has been utilized to differentiate between possible pathways for alanine biosynthesis (Valle and Heldt 1991). In animal systems, channeling of glycolytic intermediates has been demonstrated using mouse L-929 cells permeabilized with dextran sulfate (Clegg and Jackson 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Bundle-sheath strands consisting of a segment of vascular bundle surrounded by BSC of high functional integrity and metabolic competence can be obtained easily by blending leaf segments in an appropriate medium with a polytron (Valle and Heldt, 1991). The intact plasmodesmata that originally connected the bundle-sheath cytosol with MC are permeable to molecules up to a molecular mass of about 900 D (Valle et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Two grams of 1-mm leaf segments was blended in 16 mL of medium according to the method of Valle and Heldt (1991) in a polytron with 1-s (20,000 rpm) and 20-s (15,000 rpm) bursts. The bundle-sheath strands were collected on a 280-m nylon net, washed thoroughly, and resuspended at a level of approximately 50 g chlorophyll mL Ϫ1 resuspending medium (0.3 m sorbitol, 20 mm Tricine-KOH (pH 7.5), 4 mm MgCl 2 , 10 mm KCl, 2 mm KH 2 PO 4 , 1 mm ADP, 10 mm glycerate 3-phosphate, 5 mm glutamate, 5 mm malate, 2 mm O-acetyl-l-Ser, and 0.2 mm K 2 SO 4 ).…”
Section: S Labeling Of Isolated Bundle-sheath Strandsmentioning
confidence: 99%
“…3). Valle and Heldt (1991) measured similar activities of pyruvate kinase in BS strands of maize and concluded that these activities were not high enough to fully account for the formation of Ala from PEP. In addition, activities of pyruvate kinase in PEPCK-type species either are lower than rates of photosynthesis (Smith and Woolhouse, 1983) or are not detectable (Rathnam and Edwards, 1977).…”
Section: Photosynthetic Metabolism In Maizementioning
confidence: 99%